Effects of Whey Protein Isolate Mixed with Vitamin D Emulsion Gels on Improving Muscle and Performance Recovery in Resistance-Trained Males - Nuanchankong, Jutawan; Jaroennon, Pattamaporn; Manakla, Sakunta (Journal of Food Health and Bioenvironmental Science, 2023)
Exercise performance, skeletal muscle repair, and physical recovery are influenced by protein and vitamin D. This study investigated the effects of whey protein isolate mixed with vitamin D emulsion gels (WPD-emulsion gels) on body composition and performance recovery in resistance-trained males. Various formulas of WPD-emulsion gels were developed with an optimal daily dose recommended protein content of 28 g from whey protein isolate, 1000 IU of vitamin D and three different amounts of rice bran oil and gelatin. A 9-point hedonic scale study was conducted to identify the highest rating formula on sensory acceptability and the effects on body composition and performance recovery. Eight resistance-trained males aged between 20-40 years old who spent at least 70% of total exercise time on resistance training for 3-5 days per week were chosen to participate. Participants were assigned WPD-emulsion gels consumed 30 min after resistance training (4 days/week) for 4 weeks. The study instruments were as follows: anthropometric and dietary assessments, the push-up and sit-to-stand test, muscle recovery times, perceived recovery status scale and rating of perceived exertion. Statistical analysis used one-way ANOVA and Paired t-tests. The results showed that the 5% rice bran with 14% gelatin formula received the highest sensory acceptability score. Skeletal muscle mass (at week 0: 59.9±3.4 kg, at week 4: 61.4±3.0 kg) and fat free mass (at week 0: 63.1±3.6 kg, at week 4: 64.6±3.1 kg) were significantly increased from week 0 (p<0.05). In addition, participant’s legs muscle mass and exercise recovery were also significantly improved. The study recommends that the consumption of WPD emulsion gels is beneficial to muscles and could increase fat-free mass and improve exercise performance recovery.